Redo living‐donor lobar lung transplantation for bronchiolitis obliterans associated with antibody‐mediated rejection. (20th November 2013) - Chen, Fengshi; Miyagawa‐Hayashino, Aya; Yurugi, Kimiko; Chibana, Naomi; Yamada, Tetsu; Sato, Masaaki; Aoyama, Akihiro; Takakura, Shunji; Bando, Toru; Date, Hiroshi
Summary Living‐donor lobar lung transplantation (LDLLT) is an established therapy for patients with end‐stage lung disease, but living‐donor lobar lung retransplantation (re‐LDLLT) is rarely reported. We previously reported a case of unilateral antibody‐mediated rejection after LDLLT in the presence of newly formed donor‐specific antibodies against a right‐lobe donor. The same patient developed contralateral bronchiolitis obliterans, resulting in bilateral bronchiolitis obliterans, but re‐LDLLT was successful. Pathological findings of the explanted lungs were consistent with the clinical course of the patient. One year after re‐LDLLT, the patient is doing well without any anti‐human leukocyte antigen antibodies. Four lobes from four different donors were transplanted in this patient. The first two lobes were rejected eventually, but the two lobes implanted later presented no signs of rejection at least for 1 year after the transplant. Herein, we report this rare case and compare the clinical course and pathological findings.